Pengaruh Gaya Kepemimpinan Demokratis, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV. Guna Karya - Lia Dwi Pramesthie; N. Rachma; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of democratic leadership style, motivation, and work environment on employee performance at CV. Guna Karya Malang. In this study the sample is Malang City CV. Guna Karya employees. Collecting data using a questionnaire, data analysis, which used the validity of the test, reliability test, normality test, multiple regression analysis, classic assumption test, multicollinearity test, heteroscedasticity test, statistical test f, statistical test t. The results of this study have a significant positive effect on democratic leadership style, motivation, and work environment on employee performance at CV. Guna Karya Malang. There is a significant influence of democratic leadership style on the performance of CV. Guna Karya employees. There is a significant influence of motivation on the performance of CV. Guna Karya employees. There is a significant work environment on the performance of CV. Guna Karya employees.Keywords: Democratic Leadership Style, Motivation, Work Environment, Employee Performance